Design and Development of Novel Fin Micro Channel Heat Sink for High Heat Flux Application - Nor Haziq, Naqiuddin Hamli (2019)
The scale-down trend increases the chips’ density and the high power handling capability generates unnecessary heat which can disrupt the reliability of the electronic devices. Therefore, various types of cooling solution have been proposed to enhance heat dissipation from electronic devices. One of the solutions is using an inexpensive straight-channel heat sink. However, the presence of a large temperature gradient between the upstream and downstream in the straight-channel can shorten the life span of the device and subsequently reduce the reliability. In this work, a novel segmented micro-channel is introduced to improve the thermal performance of the straight-channel heat sink. Computational fluid dynamic analysis is performed to investigate the performance of the micro-channel heat sink. Next, Taguchi-grey method is applied to optimize the design of the segmented micro-channel. The results indicate that three segments of the segmented micro-channel, fin width-1 mm, fin length-2 mm, fin transverse distance-5 mm and channel width-1 mm is an optimized design of the segmented micro-channel with enhanced heat transfer performance and minimum pressure drop. It is also found that the optimized micro-channel heat sink is able to cool the chip with a heat flux of 800 W to 56.6 oC and pumping power of 0.13 W using 15 gs-1 of water. Experimental work shows that the result deviates less than 5% for average temperature and temperature variation at 15 gs-1.